A COMPARISON BETWEEN TRANSURETHRAL CYSTOLITHOCLASTY AND VESICOLITHOTOMY IN PEDIATRIC MALE PATIENTS - Muhammed khalid; Muhammad Faizan; Muhammad Asif Gurmani; Amjad Ali Siddiqui; Qadeer Ahmed Choudhary; Zulﬁqar Anjum (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: To compare transurethral cystolithoclasty with ureteroscope over open vesicolithotomy in pediatric male patients. METHODOLOGY: Study comprises of hundred pediatric male patients, divided into two equal groups of 50 each, labeled as Group-A and Group-B. All the patients having stones less than 20mm size (average 14mm) were included. Group-A patients were treated with transurethral cystolithoclasty by using ureteroscope and pneumatic lithoclast assisted with the help of Dormia basket. Group-B patients were treated with open vesicolithotomy. RESULTS: All hundred male pediatric patients were between the ages of 1-15 years (mean age 8 years). Hospital stay was 2-3 days (average 2.5 days) in Group-A patients and 3-5 days (average 4 days) in Group-B patients. In Group-A3 (6%) patients had urinary tract infection, 1(2%) had urethral injury and 2(4%) had residual stone post-operatively. While Group-B4 (8%) suﬀered from urinary tract infection, 1(2%) had wound infection, 1(2%) had hematuria, and 2(4%) had fever. Retention of urine was 1(2%) in each Group. CONCLUSION: Transurethral cystolithoclasty is a much better way of treating vesical calculus in pediatric male patients because it is a procedure with short hospital stay, minimal invasion, no scar and less complication. KEYWORDS: Bladder Calculus, Comparison, Cystolithoclasty, Ureteroscope, Pneumatic Lithoclast, Dormia basket, Vesicolithotomy.